Peningkatan Keamanan Dan Penyelamatan Korban Insiden Di Wilayah Perairan: Studi Tentang Upaya Efektif Dalam Mengatasi Korban Dan Meminimalisir Kerugian Manusia - Fadhli Dzil Ikram; Iftita Azalea Febryanti; Inas Sa’idah Auliya; Andrio Josep Pardede; Denny Oktavina Radianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Incidents in water areas often pose major challenges in terms of handling victims and rescue, especially because environmental conditions are dynamic and difficult to reach. The main problem that needs to be addressed is how to provide an effective and timely response to incidents in waters, so that victims can get help quickly and the number of missing victims can be minimized. In addition, it is also important to ensure that rescued victims receive adequate care and assistance to ensure their safety and health. To achieve this goal, it is necessary to identify and in-depth analysis of methods and strategies that can be used in handling victims of incidents in water areas. This includes developing systems or procedures that are effective in providing assistance, as well as minimizing difficulties in finding missing victims. By better understanding the dynamics of incidents in water areas and the factors that influence victim safety, it is hoped that more effective strategies can be developed in dealing with emergency situations in water areas.